2022
DOI: 10.1038/s41419-022-04582-6
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of caspase cascade overcomes malaria-associated acute respiratory distress syndrome in mice

Abstract: Malaria is an enormous burden on global health that caused 409,000 deaths in 2019. Severe malaria can manifest in the lungs, an illness known as acute respiratory distress syndrome (ARDS). Not much is known about the development of malaria-associated ARDS (MA-ARDS), especially regarding cell death in the lungs. We had previously established a murine model that mimics various human ARDS aspects, such as pulmonary edema, hemorrhages, pleural effusion, and hypoxemia, using DBA/2 mice infected with Plasmodium berg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The results depended on the type of endothelial cell, culture conditions and Plasmodium parasites (N'Dilimabaka et al 2014). Other studies showed that iRBCs induce lung endothelial cell apoptosis through caspase 3, 8 and 9 activation with increasing cellular permeability (Pino et al 2003;Sercundes et al 2022). Interestingly, apoptotic brain endothelial cells were not associated with loss of BBB integrity in mice with cerebral malaria (Shaw et al 2015).…”
Section: Discussionmentioning
confidence: 98%
“…The results depended on the type of endothelial cell, culture conditions and Plasmodium parasites (N'Dilimabaka et al 2014). Other studies showed that iRBCs induce lung endothelial cell apoptosis through caspase 3, 8 and 9 activation with increasing cellular permeability (Pino et al 2003;Sercundes et al 2022). Interestingly, apoptotic brain endothelial cells were not associated with loss of BBB integrity in mice with cerebral malaria (Shaw et al 2015).…”
Section: Discussionmentioning
confidence: 98%
“…The results depended on the type of endothelial cell, culture conditions, and Plasmodium parasites (N’Dilimabaka et al 2014 ). Other studies showed that iRBCs induce lung endothelial cell apoptosis through caspase 3, 8, and 9 activation with increasing cellular permeability (Pino et al 2003 ; Sercundes et al 2022 ). Interestingly, apoptotic brain endothelial cells were not associated with loss of BBB integrity in mice with cerebral malaria (Shaw et al 2015 ).…”
Section: Discussionmentioning
confidence: 98%
“…Contrarily, dysfunction or dysregulation of cell apoptosis led to pathological conditions in numerous lung diseases [ 34 ]. The accumulated evidence showed that MA-ALI was partly characterized by excessive and uncontrolled inflammation and apoptosis in lung tissue [ 35 , 36 ]. A substantial increase in apoptosis or apoptotic biomarkers (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial increase in apoptosis or apoptotic biomarkers (e.g. TNF, FAS, Bax, Bad, FAS/FASL and caspases-3/8) was commonly observed in leukocytes, alveolar cells and endothelial cells of lung tissue from severe P. falciparum malaria patients with pulmonary edema and experimental MA-ALI mice [ 35 , 36 ]. An in vitro study also showed that apoptosis was detected in human primary pulmonary endothelial cells co-cultured with P. falciparum field isolates [ 37 ].…”
Section: Discussionmentioning
confidence: 99%